1983
DOI: 10.1007/bf00194626
|View full text |Cite
|
Sign up to set email alerts
|

IMF control of the Earth's magnetosphere

Abstract: We review recent progress m the understanding of the IMF control on the Earth's magnetosphere through the reconnecuon process Major points include, (l) the ~dentificatlon of the magnetopause structure under the southward IMF polarity to be the rotational discontinuity and the resulting reference that the reconnecuon line is formed in the equatorial region, and (2)the confirmation from several observational aspects that under the northward IMF the reconnection takes place m the polar cusp. The point (I) is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…[2] Many publications over many years have demonstrated the relationship between ionospheric transpolar voltage and the electric field (as measured in the Earth's frame of reference) in the interplanetary medium impinging on the magnetosphere [Reiff et al, 1981;Cowley, 1981Cowley, , 1984Doyle and Burke, 1983;Nishida, 1983;Wygant et al, 1983;Reiff et al, 1985;Reiff and Luhmann, 1986;Ahn et al, 1992;Boyle et al, 1997;Hairston et al, 1998;Lu et al, 2002aLu et al, , 2002bPapitashvili and Rich, 2002;Shepherd et al, 2002;Bristow et al, 2004;Nakata et al, 2004;Hairston et al, 2005;Ridley, 2005;Ruohoniemi and Greenwald, 2005;Zhang et al, 2007]. These studies, either explicitly or implicitly, assumed steady state conditions because the ionospheric flow pattern and voltage are studied as a function of the prevailing conditions (interplanetary or geomagnetic) with no allowance made for the prior history of those conditions [Lockwood, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Many publications over many years have demonstrated the relationship between ionospheric transpolar voltage and the electric field (as measured in the Earth's frame of reference) in the interplanetary medium impinging on the magnetosphere [Reiff et al, 1981;Cowley, 1981Cowley, , 1984Doyle and Burke, 1983;Nishida, 1983;Wygant et al, 1983;Reiff et al, 1985;Reiff and Luhmann, 1986;Ahn et al, 1992;Boyle et al, 1997;Hairston et al, 1998;Lu et al, 2002aLu et al, , 2002bPapitashvili and Rich, 2002;Shepherd et al, 2002;Bristow et al, 2004;Nakata et al, 2004;Hairston et al, 2005;Ridley, 2005;Ruohoniemi and Greenwald, 2005;Zhang et al, 2007]. These studies, either explicitly or implicitly, assumed steady state conditions because the ionospheric flow pattern and voltage are studied as a function of the prevailing conditions (interplanetary or geomagnetic) with no allowance made for the prior history of those conditions [Lockwood, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Space weather basically begins with this interaction. Studies have shown that the interplanetary magnetic field (IMF) strongly controls the state of the magnetosphere (Nishida, 1983). While the solar wind pressure can determine the size of the magnetosphere, less is understood about how the pressure influences the electrodynamics of the magnetosphere-ionosphere system.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of southward directed interplanetary magnetic field, when the solar wind energy can be directly coupled to the magnetosphere, the role of the cross tail current sheet has been recognized as fundamental in energy storage, plasma energetization andmagnetic fieldreconftguration (e.g., McPherron, 1972;Russell and McPherron, 1973;Lui, 1978;Sauvaud and Winckler, 1980;Nishida, 1983;Fairfield, 1984;Kaufmann, 1987;Lui et al, 1992).…”
Section: Introductionmentioning
confidence: 99%